The development of a mouse model to explore resistance and susceptibility to early Ascaris suum infection - HOLLAND, CELIA; STAFFORD, PETER (My University, 2006)
Ascaris suum and Ascaris lumbricoides exhibit an over-dispersed frequency distribution in their host populations in both the adult and larval stages. The impact of host factors on this observed distribution is still poorly understood and difficult to investigate in the natural host populations. The use of a mouse model has been supported by the observations that the larval migratory pattern, in this host, mimics the pattern observed in the pig. We explored the extrinsic factors that might affect the quantitative recovery of larvae during this migration in order to standardize a model system facilitating accurate future assessment of host genetic variation on this phase of the infection. In Exp. 1 larvae accumulated in the livers of both C57BL/6j and BALB/c mice up to and including days 4-5 p.i. and then declined in both strains until day 9. Loss of larvae from the livers corresponded to arrival in the lungs and maximum accumulation on day 7 p.i. but recovery was considerably higher in C57BL/6j mice. It was concluded that day 7 recoveries gave the best indication of relative resistance/susceptibility to this parasite. In Exp. 2 A/J, BALB/c, CBA/Ca, C57BL/6j, C3H/HeN, DBA/2, NIH, SJL, and SWR mice were compared. C57BL/6j mice were identified as the most susceptible strain and CBA/Ca mice as having the most contrasting phenotype, but with a similar kinetic pattern of migration. Finally, in Exp. 3, a strong positive correlation between the size of the inoculum and the mean worm recovery from the lungs was found in CBA/Ca and C57BL/6j mice, but the difference between these strains was highly consistent, 66.6-80%, regardless of the initial dose. These results demonstrate that, using our protocols for infection and recovery, between-experiment variation in A. suum worm burdens is minimal, and that C57BL/6j mice are highly susceptible to infection compared to other strains. The mechanistic basis of this susceptibility in relation to the resistance of other strains is unknown, but the possibilities are reviewed.
PUBLISHED
Keywords: Zoology; Ascaris suum; Ascaris lumbricoides